Using Digital Image Processing with Matlab to Analyse the Motion of the Object - Tran, Công Danh; Ngo , Khánh Hiếu (Journal of Technical Education Science, 2012)
Based on the “Pure pitching model” introduced by Nelson, this paper presents firstly its experimental model; secondly the use of a high-speed camera to record a fast motion like “pitch motion”; and finally the analysis of digital image processing with Matlab in order to capture the pitch motion. In comparison with the pure pitching oscillation from Nelson, the experimental results in this paper allow to insist on the role of the high-speed camera and the Image Processing with MatLab in observing the motion